2018
DOI: 10.1093/bioinformatics/bty155
|View full text |Cite
|
Sign up to set email alerts
|

Bastion6: a bioinformatics approach for accurate prediction of type VI secreted effectors

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
68
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(73 citation statements)
references
References 51 publications
0
68
1
2
Order By: Relevance
“…Bayesian inference analysis was computed using MrBayes software (v3.2.6) [28] under a LG+I+G+F substitution model for 10 5 generations, burn-in 25%. Amino acid sequences were also analyzed with the T3S effector prediction programs SIEVE [29], pEffect [30], EffectiveT3 [31] and ModLab T3S [32], as well as the T4S effector prediction programs T4SEpre [33] and T4 EffPred [31], and the T6SS predictor tools Bastion6 [34] and SecReT6 [35]. Amino acid sequences for L. pneumophila VipE, Salmonella enterica SopE and Legionella londiniensis Hcp were used as positive controls for the T3SS, T4SS, and T6SS effector predictors, respectively.…”
Section: In Silico P Salmonis Hsp60 Amino Acid Sequence Analysesmentioning
confidence: 99%
“…Bayesian inference analysis was computed using MrBayes software (v3.2.6) [28] under a LG+I+G+F substitution model for 10 5 generations, burn-in 25%. Amino acid sequences were also analyzed with the T3S effector prediction programs SIEVE [29], pEffect [30], EffectiveT3 [31] and ModLab T3S [32], as well as the T4S effector prediction programs T4SEpre [33] and T4 EffPred [31], and the T6SS predictor tools Bastion6 [34] and SecReT6 [35]. Amino acid sequences for L. pneumophila VipE, Salmonella enterica SopE and Legionella londiniensis Hcp were used as positive controls for the T3SS, T4SS, and T6SS effector predictors, respectively.…”
Section: In Silico P Salmonis Hsp60 Amino Acid Sequence Analysesmentioning
confidence: 99%
“…Upstream to this gene, there is another small protein (138 amino acids) containing a DUF2195 annotated as STM14_0335 , which encodes a predicted Sec signal peptide sequence for periplasmic localization (Figure S1A) (Almagro Armenteros et al, 2019). Bastion6 software prediction (Wang et al, 2018) indicates that STM14_0336 could be a T6SS effector (score 0.758). To test whether STM14_0336 and STM14_0335 are a bona fide effector/immunity pair we cloned these genes in compatible vectors under the control of different promoters.…”
Section: Resultsmentioning
confidence: 99%
“…81,82 However, validation of MIX reliability was done against Bastion6, the first machine-learning tool that promises accurate prediction of T6SS effectors. 83 MIX motif ability in the identification of T6SS effectors or importance for translocation and effector function was very low. 83 On the other hand, Nguyen et al used the poorly rated marker and reported 57 novel MIX T6SS effectors and two identified T6SS phospholipases.…”
Section: Pipelines Currently Assisting the Discovery Of Antieukaryotimentioning
confidence: 99%